Prognostic Role of Serum Lactate Dehydrogenase in Patients With Urothelial Carcinoma: A Systematic Review and Meta-Analysis - Wu, Minhong; Lin, Pengxiu; Xu, Lifang; Yu, Zhiling; Chen, Qingsheng; Gu, Hongyong; Liu, Cailing (Frontiers in Oncology, 2020)
Background: To investigate the potential prognostic role of serum lactate dehydrogenase (LDH) in patients with urothelial carcinoma (UC) using the method of systematic review and meta-analysis. Materials and Methods: We searched PubMed, Embase, Cochrane Library and Web of Science for eligible studies up to February 2020. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were used to estimate the relationship. Results: A total of 14 studies including 4,009 patients with UC were incorporated. The results showed that a high pretreatment serum LDH was associated with an inferior overall survival (OS, HR 1.61, 95% CI 1.39-1.87, p < 0.001), cancer-specific survival (CSS, HR 1.41, 95% CI 1.05-1.90, p = 0.022), and disease-free survival (DFS, HR 1.64, 95% CI 1.04-2.59, p = 0.034) in UC. Subgroup analyses identified that a high pretreatment serum LDH was associated with a poor OS (HR 1.97, 95% CI 1.02-3.81, p = 0.042) and DFS (HR 1.64, 95% CI 1.04-2.59, p = 0.034) in UTUC, a short OS (HR 1.71, 95% CI 1.37-2.15, p < 0.001) in UCB. Conclusion: Our findings indicated that a high level of pretreatment serum LDH was associated with an inferior OS, CSS and DFS in patients with UC. This biomarker can be important factor incorporated into the prognostic models for UC.